The Major Intrinsic Protein Family and Their Function Under Salt-Stress in Peanut - Han, Yan; Li, Rongchong; Liu, Yiyang; Fan, Shoujin; Wan, Shubo; Zhang, Xuejie; Li, Guowei (Frontiers in Genetics, 2021)
Peanut (Arachis hypogaea) is an important oil crop cultivated across the world. Abiotic stresses are the major constraint factors that affect its yield, especially in the rainfed peanut cultivation areas. Aquaporins are proteins that form a large family of more than 30 members in higher plants and play key roles in plant water balance under abiotic stress conditions. To comprehensively understand the functions of aquaporins in peanut, we identified their genome-wide family and characterized the phylogenetics, gene structure, and the conserved motif of the selective filter. In total, 64 aquaporin isoforms were identified, the NIPs were firstly categorized into NIP1s and NIP2s groups based on the phylogenetic analysis and the selective filter structure classification system. Further, we analyzed the gene expression pattern under the salt-stress conditions and found that a TIP3 member is strongly induced by salt stress, which in turn contributed to improved seed germination under salt stress when expressed in Arabidopsis. Our study thus provides comprehensive profiles on the MIP superfamily and their expression and function under salt-stress conditions. We believe that our findings will facilitate the better understanding of the roles of aquaporins in peanuts under salt salt-stress conditions.